GAMBARAN STRES PADA MAHASISWA TINGKAT AKHIR YANG SEDANG MENGERJAKAN SKRIPSI - Hariaty, Hariaty; Elita, Veny; Dilaluri, Ade (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Astudent's stressor is working on a thesis as one of the requirements for college graduation. The body's response to stress includes increased heart rate, diarrhea and insomnia. One stress management that can be used is to do positive affirmations. The purpose of this study was to determine the effect of positive affirmations to reduce stress on final year students who are working on a thesis at the Faculty of Nursing, Riau University. Methods: This study uses a descriptive research design with a cross-sectional approach, the sample of this research is the final semester students of class A 2018 1 and 2, with perposive sampling technique. The data collection tool used is the DASS (Depression Anxiety Stress Scale) questionnaire. Analysis of the data used is univariate analysis. Results: This shows that most of the final year students who are working on theses are experiencing moderate stress, namely 27 people (79.4%) and a little bit 7 people (20.6%) which means that p value (0.001) < alpha (0.05 ). Conclusion: most students experience moderate stress on students who are working on their thesis.